THE ILLUSORY DISTINCTION BETWEEN RE- AND PREDISTRIBUTION - Melkevik, Åsbjørn (Les ateliers de l'éthique / The Ethics Forum, 2021)
The distinction between redistribution and predistribution is now embraced by many political philosophers, like Jacob Hacker or Martin O’Neill. This distinction, we could think, is particularly important for the question of how we react to crises, like the current coronavirus pandemic. If the policies take the form of taxes and transfers, like cash-flow assistance, it is redistribution, one could argue. If the policies are meant to alter pretax incomes, as policies changing the conditions for bankruptcy are, it is predistribution. This paper shows why that is not so. Re- and predistribution are only techniques of presentation. They are meant to put the emphasis on different ways we can depict the consequences of policies. Both the “pre-” of predistribution and the “re-” of redistribution are misnomers. This paper argues that we cannot establish a strong distinction between policies that are re- and those that are predistributive, as the case of the basic income will show. Given that classical liberals endorsed egalitarian policies, moreover, the idea of predistribution cannot be used by progressives who want to differentiate their social justice platforms from the classical liberal program.